Possible Differences in Visual Attention to Faces in the Context of Mate Choice and Competition - Pátková, Žaneta; Grygarová, Dominika; Adámek, Petr; Třebická Fialová, Jitka; Havlíček, Jan; Třebický, Vít (Archives of sexual behavior, 2025)
Existing research indicates that the shape of various facial regions is linked to perceived attractiveness and perceived formidability. Interestingly, little evidence shows that people directly focus on these specific facial regions during judgments of attractiveness and formidability, and there is little support for the notion that the levels of attractiveness and formidability affect raters' visual attention. We employed eye-tracking to examine visual attention (the number of fixations and dwell time) in 40 women and 37 men, while they assessed 45 male faces in life-sized photographs for attractiveness and formidability. The facial photographs were grouped by varying levels of attractiveness and formidability (low, medium, and high). Our results showed that regardless of the characteristics rated, both men and women paid the most visual attention to the eyes, nose, mouth, and forehead regions. We found statistically discernible variation in visual attention in relation to the rater's sex or target's attractiveness levels for other facial features (the chin, cheeks, or ears), but these differences may not be substantial enough to have practical implications. We suggest that the eyes, the nose, and the mouth regions play a central role in the evolution of face perception as regions most salient to the acquisition of informative cues about others. Further, during both attractiveness and formidability judgments, men looked longer at the stimuli than women did, which may hint at increased difficulty of this task for men, possibly because they compare themselves with the stimuli. Additionally, irrespective of sex, raters looked marginally longer at faces with a medium level of formidability than at those with a high formidability level, which may reflect ambiguity of these stimuli and uncertainty regarding assessment. We found no other significantly relationships between the target's attractiveness and formidability levels and the rater's visual attention to whole faces.
Keywords: Formidability; krása; Humans; Attention; obličej; výběrové chování; Female; mladý dospělý; dospělí; zraková percepce; Eye-Tracking Technology; lidé; kompetitivní chování; rozpoznání obličeje; Visual Perception; Facial Recognition; Intersexual selection; Choice Behavior; Adult; ženské pohlaví; Male; Competitive Behavior; technologie sledování pohybu očí; Young Adult; Beauty; Face; Eye-tracking; mužské pohlaví; pozornost; Intrasexual selection; Attractiveness